Recurrent Gastrointestinal Hemorrhage in Children with Philadelphia-Positive B-Cell Acute Lymphoblastic Leukemia Treated with Dasatinib: Case Reports - Xin Liao; Yuxia Guo; Yali Shen; Jianwen Xiao (Case Reports in Hematology)
Dasatinib, a second-line tyrosine kinase inhibitor (TKI), has been widely used in chronic myeloid leukemia (CML) and Philadelphia-positive B-cell acute lymphoblastic leukemia (Ph + B-ALL). Although dasatinib has been well tolerated, side effects including hemorrhage are not rare. Cases of bleeding disorders ultimately result in thrombocytopenia, but platelet aggregation dysfunction induced by dasatinib has also been demonstrated in Ph + B-ALL and CML patients. We report three Chinese children with Ph + B-ALL who received a combination treatment of chemotherapy and dasatinib and developed gastrointestinal bleeding several months later. The platelet count and clotting tests were normal, and these patients presented with dasatinib-induced platelet dysfunction. These findings reveal that physicians should be aware of and carefully monitor for side effects, including bleeding disorders.